Tracking Polar Lows in CLM - Zahn, M.; Storch, H.v. (Meteorologische Zeitschrift, 2008)
Polar lows are severe cyclones in sub-polar oceans sized beyond the resolved scale of existing global reanalysis products. We used the NCEP/NCAR reanalyses data to drive a regional climate model (CLM) in order to reproduce finer resolved atmospheric fields over the North Atlantic over a two year period. In these fields we detected polar lows by means of a detection algorithm based on a spatial digital bandpass filter. CLM was run in two different ways, the conventional way and with additionally prescribing the analysed large scale situation. The resulting temporal and spatial distributions of polar lows between the different simulations are compared. A reasonable seasonal cycle and spatial distribution was found for all simulations. A lower number of polar lows in the spectral nudged simulation indicates a closer vicinity to reality. Higher temporal and spatial variability between the conventional simulations suggest a more random generation of polar lows. Frequency distributions of track-lengths reveal shorter tracks when nudging is applied. Maximum wind speeds reveal only minor, insignificant differences between all runs and are higher in conventional mode.